2006
DOI: 10.1016/j.visres.2006.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Centrins, gatekeepers for the light-dependent translocation of transducin through the photoreceptor cell connecting cilium

Abstract: Centrins are members of a highly conserved subgroup of the EF-hand superfamily of Ca(2+)-binding proteins commonly associated with centrosome-related structures. In the retina, centrins are also prominent components of the photoreceptor cell ciliary apparatus. Centrin isoforms are differentially localized at the basal body and in the lumen of the connecting cilium. All molecular exchanges between the inner and outer segments occur through this narrow connecting cilium. Ca(2+)-activated centrin isoforms bind to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…Several further discrete localisations have also been identified, in cilia (Gonda et al, 2004;Guerra et al, 2003;LeDizet and Piperno, 1995) and ciliary-derived organelles of sensory cells (Giessl et al, 2006), at the contractile vacuole pores in Tetrahymena (Stemm-Wolf et al, 2005) and at the Golgi in Trypanosoma (He et al, 2005;Selvapandiyan et al, 2007). Interestingly, if species differ widely in their number of centrin genes (one in yeast, four in mammals, seven in Leishmania, at least ten in Tetrahymena and 49 in Paramecium), when more than a single gene is present, a particular localisation or function may involve either a single or different centrin isotypes and conversely, a particular isotype may show different localisations or functions.…”
Section: +mentioning
confidence: 92%
“…Several further discrete localisations have also been identified, in cilia (Gonda et al, 2004;Guerra et al, 2003;LeDizet and Piperno, 1995) and ciliary-derived organelles of sensory cells (Giessl et al, 2006), at the contractile vacuole pores in Tetrahymena (Stemm-Wolf et al, 2005) and at the Golgi in Trypanosoma (He et al, 2005;Selvapandiyan et al, 2007). Interestingly, if species differ widely in their number of centrin genes (one in yeast, four in mammals, seven in Leishmania, at least ten in Tetrahymena and 49 in Paramecium), when more than a single gene is present, a particular localisation or function may involve either a single or different centrin isotypes and conversely, a particular isotype may show different localisations or functions.…”
Section: +mentioning
confidence: 92%
“…This interaction was confirmed by GST pulldown, co-sedimentation, size exclusion chromatography and light-scattering experiments. CETN1 was therefore hypothesized to regulate light-dependent translocation of membrane-associated transducin (Giessl et al, 2006;Trojan et al, 2008). However, as shown (Fig.…”
Section: Yeastmentioning
confidence: 98%
“…Light-activation of rhodopsin triggers GTP/GDP exchange on Ta causing Ta GTP and Tbc to dissociate and traffic to the inner segment in minutes (Calvert et al, 2006). We have shown that Ca 2+ -activated centrin isoforms (CETN1,2,4) bind tightly to transducin via the Tbc-subunits, and suggested that Ca 2+ -dependent assemblies of centrin/G-protein complexes may regulate transducin movement through the connecting cilium (Giessl et al, 2006;Trojan et al, 2008). Immunohistochemistry using antibodies directed against rod Ta and Tc showed no significant difference in light-induced translocation of transducin to the inner segments of Cetn1 +/+ and Cetn1 2/2 mice ( Fig.…”
Section: Photoreceptor and Germline Deletion Of The Cetn1 Genementioning
confidence: 99%
See 1 more Smart Citation
“…For example, after light-induced translocation, transducin forms a stable complex with UNC119 and diffuses back into the OS. 88 Movement of transducin is also thought to be regulated by the Ca 2+ -binding centrin proteins that are localized to the basal body and axoneme of the CC 89 and are phosphorylated by CK2. 90 UNC119 also binds myristoylated ciliary proteins, such as nephrocystin-3 (NPHP3), to target them to the ciliary membrane and maintain the spatial organization of the cilium.…”
Section: Transport In the Photoreceptormentioning
confidence: 99%